Preparation of monodisperse ferrous nanoparticles embedded in carbon aerogels via in situ solid phase polymerization for electrocatalytic oxygen reduction. Issue 28 (10th July 2020) - Hong, Wei; Feng, Xin; Tan, Lianqiao; Guo, Aiming; Lu, Bing; Li, Jing; Wei, Zidong
Abstract : Core–shell structured materials constructed by using Fe/Fe3 C cores and nitrogen doped carbon shells represent a type of promising non-precious oxygen reduction reaction (ORR) catalyst due to well-established active sites at the interface positions. Abstract : Core–shell structured materials constructed by using Fe/Fe3 C cores and nitrogen doped carbon shells represent a type of promising non-precious oxygen reduction reaction (ORR) catalyst due to well-established active sites at the interface positions. However, the traditional liquid phase polymerization route for preparing such materials normally leads to a compact macropore-deficient structure with randomly dispersed metallic nanoparticles, which is not beneficial for mass transfer and the formation of a high-density dispersion of active sites. Herein, we report an " in situ solid phase polymerization strategy" in which a frozen block containing uniformly dispersed oligomers is firstly achieved by combining a well-controlled hydrothermal reaction and a subsequent liquid nitrogen-facilitated fast solidification. During the following freeze-dry process, the oligomers in situ polymerize into a 3D highly cross-linked network in the confined space of the ice block which not only effectively avoids the direct stacking of polymerized intermediates, but also prevents the agglomeration of metallic nanoparticles. The finally obtained monodisperse Fe/Fe3 C nanoparticles embedded in nitrogen-doped carbon aerogel catalyst, in the ORR, delivers an ultrahigh activity as the half-wave potential and the kinetic current density at 0.9 V reach 0.919 V and 7.83 mA cm −2 respectively in an alkaline solution. Using this route, a range of aerogel materials with improved performances for various applications may be explored.